Toward sustainable bioproducts from lignocellulosic biomass: Influence of chemical pretreatments on liquefied walnut shells - Jovičić Nives; Krička Tajana; Antonović Alan; Matin Božidar; Pezo Lato; Brandić Ivan; Matin Ana (Open Agriculture)
The depletion of resources and the generation of significant waste pose considerable environmental challenges. Post-utilization of walnut kernels leaves behind substantial amounts of shells as the unused residue. Walnut shells find application in various production processes, offering an opportunity to mitigate environmental impacts through resource utilization. This study investigates the influence of chemical pretreatment on the properties of liquefied lignocellulosic biomass, specifically focusing on walnut shells as a prominent lignocellulosic material. The results reveal that samples subjected to alcohol pretreatment exhibited the lowest degree of liquefaction (85.00% at 120°C for 45 min), while the highest degree of liquefaction was observed in samples after alkaline pretreatment (90.76% at 90°C for 15 min). Analyzing functional groups in liquefied walnut shell biomass, formed during the addition of polyhydric alcohols, glycols, and organic acids, underscores its potential for diverse bioproducts. Pretreatment significantly increases the hydroxyl (OH) number, irrespective of the type, temperature, and duration of chemical pretreatment. Compared to the untreated sample, alkali pretreatment produces the highest OH number (1288.03 KOH/g), surpassing mean values after acid and alcohol pretreatment. The results highlight the efficacy of chemical pretreatment in tailoring the properties of liquefied walnut shell biomass, addressing the challenges associated with resource depletion and waste accumulation.